Stylistic Analysis of the Story of Prophet Musa and Khiḍr in the Qur’an, Surah Al-Kahf - L. Alfalaq Bangkit Sanjaya; Asep Sopian; Rinaldi Supriadi (Universitas Cokroaminoto Palopo, 2025)
This study aims to analyze the stylistics of the story of Prophet Musa and Khiḍr in Surah Al-Kahf, verses 60–82, focusing on morphological and semantic aspects. This study uses a descriptive-qualitative approach and content analysis. The data was collected through documentation techniques from primary sources such as Qur'anic verses and secondary sources such as tafsīr books, dictionaries, and relevant previous studies. The study results show that the morphological aspects of this story include letter omission, the choice of indefinite words, specific word patterns and forms, and shifts in pronouns, which create profound effects and impressions such as urgency, uniqueness, sincerity, brevity, broad meaning, and politeness. Meanwhile, from a semantic aspect, using synonyms, antonyms, and polysemy highlights the precision of word choice and enhances the message's clarity. These stylistic elements contribute to the beauty and persuasive power of the Qur'an, thereby deepening its meaning. This study emphasizes the importance of stylistic analysis in understanding the beauty of language, particularly in terms of word choice.